Evaluation of an innovative, green, and eco-friendly baclofen-loaded niosome (Baclosome) formulation for pain management by transdermal delivery - Jafar Akbari; Majid Saeedi; Katayoun Morteza-Semnani; Seyede Nastaran Mousavi; Seyyed Mohammad Hassan Hashemi; Seyyed Mobin Rahimnia (Nanomedicine Journal)
Objective(s): Baclofen, a muscle relaxant, exhibits limited dermal penetration, restricting its therapeutic efficacy. This study aimed to optimize baclofen delivery using ultrasonically manufactured niosomes (Baclosomes) for improved antinociceptive and anti-inflammatory activity. Materials and Methods: The effect of cholesterol:surfactant (Chol:Surf) ratio on Baclosome characteristics was investigated using powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy. Dermal permeation studies were conducted in rats to assess baclofen delivery to the dermis and recipient compartment. Antinociceptive and anti-inflammatory effects were evaluated using a rat model.Results: Increasing Chol content significantly increased Baclosome particle size. The Chol:Surf ratio also influenced zeta potential (ZP), ranging from -9.10 ± 1.81 to -28.81 ± 1.3mV. DSC and PXRD analyses confirmed the amorphous nature of baclofen within the Baclosomes. There was no chemical interaction between the drug and the excipients which supported by ATR-FTIR analysis. Dermal permeation studies showed higher baclofen levels in the dermis and recipient compartment for Baclosome gel compared to plain baclofen gel, without inducing dermal irritation. Baclosome gel demonstrated significant antinociceptive and anti-inflammatory effects compared to control groups (baclofen gel and diclofenac gel).Conclusion: This study demonstrated that ultrasonically manufactured Baclosomes effectively enhance baclofen delivery to the skin, resulting in improved antinociceptive and anti-inflammatory activity. Optimization of the Chol:Surf ratio significantly influenced Baclosome characteristics, highlighting the potential of this formulation approach for enhancing drug efficacy. This approach could offer a promising strategy for improving the therapeutic benefits of baclofen in treating musculoskeletal pain and inflammation.